Nationalization, Collectivization, Reprivatization, and Privatization in East Central Europe: Arguments for a General Theory - Veress, Emőd (Lectures on East Central European Legal History, 2022)
Following the Second World War, a significant transformation occurred in private law under the Soviet-type dictatorial regime. Suppression – akin to abolition – of private property, wide-scale nationalization, and collectivization are presented in this chapter through the legal norms by which the socialist transfiguration of the national economy was meant to be achieved. Following the regime changes, a reversion to historical patterns of regulation and then the gradual evolution of civil law took place. We examine the legislative measures for achieving the transition to a market economy. We present in detail the private law implications of the (incomplete and imperfect) restitution of nationalized property and privatization. The chapter presents the general East Central European trends and, to provide specific details, uses Romania’s historical and legal evolutions as a case study. KEYWORDS: civil law, communism, state property, nationalization, collectivization, reprivatization, privatization, East Central Europe, Romania.